2009
DOI: 10.1016/j.joca.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of tumor necrosis factor-α in the rat: an acute and reversible in vivo model of cartilage proteoglycan degradation

Abstract: TNFalpha injection in the knee joints of rats results in rapid transient cartilage proteoglycan degradation, mediated by cleavage at the aggrecanase sites. Biomarker read-out of specific neoepitopes in the SF enables the use of this mechanism-based model for rapid evaluation of aggrecanase-mediated aggrecan degradation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…These findings are furthermore consistent with previous in vitro and in vivo investigations showing that high concentrations of catabolic cytokines such as TNF-α lead to early (8 h to 2 days) aggrecanase activity [49, 50]. In agreement with Madsen et al [50], who used a similar bovine explant system, we did not detect MMP-generated FFGV fragments in the medium or in the cartilage during the 6 days of cartilage explant culture in the presence of TNF-α.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are furthermore consistent with previous in vitro and in vivo investigations showing that high concentrations of catabolic cytokines such as TNF-α lead to early (8 h to 2 days) aggrecanase activity [49, 50]. In agreement with Madsen et al [50], who used a similar bovine explant system, we did not detect MMP-generated FFGV fragments in the medium or in the cartilage during the 6 days of cartilage explant culture in the presence of TNF-α.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the inhibitory effect of DEX on matrix degradation may involve modulating the proteolytic activities of aggrecanases. Recently, Malfait et al demonstrated that DEX blocked aggrecanase activity in an in vivo model of cartilage degradation: intra-articular injection of TNFα in rats resulted in aggrecanase-generated proteoglycan degradation, which could be inhibited by either an aggrecanase inhibitor or DEX, but not a non-steroidal anti-inflammatory drug [44]. …”
Section: Discussionmentioning
confidence: 99%
“…These models typically present as a mild, acute lesion relative to the joint alterations produced by other inciting agents. A sixth alternative is to inject proinflammatory cytokines directly into a joint (usually the tibiotarsal joint (knee) due to its large volume) to induce an acute synovitis [62, 63]. Interestingly, IL-1 β and TNF- α produce distinct, time-dependent patterns of acute arthritis in the rat knee following direct injection [62].…”
Section: Objective 1: Available Rodent Models Of Immune-mediated Amentioning
confidence: 99%